2022
DOI: 10.3390/nu14020348
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Diet in Prognosis among Cancer Survivors: A Systematic Review and Meta-Analysis of Dietary Patterns and Diet Interventions

Abstract: Cancer survival continues to improve in high-income countries, partly explained by advances in screening and treatment. Previous studies have mainly examined the relationship between individual dietary components and cancer prognosis in tumours with good therapeutic response (breast, colon and prostate cancers). The aim of this review is to assess qualitatively (and quantitatively where appropriate) the associations of dietary patterns and cancer prognosis from published prospective cohort studies, as well as … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(64 citation statements)
references
References 75 publications
(151 reference statements)
3
61
0
Order By: Relevance
“…In the context of nutrition, the assessment of quality of life also becomes significant. It has been proven that physical exercise and healthy eating lead to a reduction of body fat and an improvement in the quality of life of women [ 38 ]. A lifestyle change involving physical exercise and a low-calorie, healthy diet resulted in a reduction in depressive symptoms and normalisation of hypothalamic–pituitary–adrenal axis regulation in women who were completing breast cancer treatment [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the context of nutrition, the assessment of quality of life also becomes significant. It has been proven that physical exercise and healthy eating lead to a reduction of body fat and an improvement in the quality of life of women [ 38 ]. A lifestyle change involving physical exercise and a low-calorie, healthy diet resulted in a reduction in depressive symptoms and normalisation of hypothalamic–pituitary–adrenal axis regulation in women who were completing breast cancer treatment [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several factors, such as dietary changes, increased physical activity, vitamin D use and coffee intake, have been shown to be beneficial in the setting after colorectal cancer surgery. Although there are no randomized clinical trials that have evaluated the role of diet after surgery, at least two studies have shown that patients who were on a diet with increased processed meat, red meat, sweets and refined grains had increased recurrence rates and decreased disease-free survival (DFS) [ 31 , 32 , 33 ]. High glycemic index diets were also associated with decreased DFS among obese and overweight patients [ 33 , 34 ].…”
Section: Nutrition Treatment Of Patients With Colorectal Cancermentioning
confidence: 99%
“…Regarding dietary patterns interventions in cancer patients and survivors, a recent review and metanalysis highlighted that there is a good evidence of the effect of healthy diets on overall survival and quality of live for survivors of certain cancers, such as breast and colon cancer [ 54 ]. Although variability exists among studies and healthy diets’ definitions, some aspects are common, such as increased intakes of fruit, vegetables, and fish and reduced intake of saturated fats.…”
Section: The Role Of Lipogenesis and Ketogenic Diets In Cancermentioning
confidence: 99%